Comparison of Musharakah Mutanaqisah (MMQ) Regulatory Framework in Indonesia, Malaysia, and Brunei: Challenges and Solutions - Umar Firmansyah, Ahmad (Al-Muhtarifin: Islamic Banking and Islamic Economic Journal, 2024)
This study aims to examine the regulatory framework of Musyarakah Mutanaqisah (MMQ) in Indonesia, Malaysia, and Brunei, and compare the implementation and challenges faced in the three countries. MMQ is one of the important Islamic financing products in Islamic banking, where the portion of asset ownership is gradually purchased by customers from banks until full ownership changes hands. This study uses a doctrinal legal approach with legislative, conceptual, and comparative methods to analyze the regulations, fatwas, and policies that govern MMQ. In Indonesia, MMQ regulations are based on the fatwa of the National Sharia Council of the Indonesian Ulema Council (DSN-MUI) and the regulations of the Financial Services Authority (OJK). DSN-MUI Fatwa No. 73/DSN-MUI/XI/2008 and No. 101/DSN-MUI/X/2016 provide detailed guidance on the implementation of MMQ, but challenges such as legal certainty of asset ownership and risk management still need to be overcome. In Malaysia, Bank Negara Malaysia (BNM) through the Sharia Advisory Council (SAC) issues policy documents such as BNM/RH/STD028-7 which govern the MMQ. The integration of MMQ with other contracts such as ijarah and istisna adds complexity to its implementation. Meanwhile, in Brunei, the Brunei Islamic Religious Council (MUIB) issued fatwas and regulations tailored to the local context. The main challenge in Brunei is the lack of public understanding of MMQ and legal documentation issues. The study concludes that although all three countries share the same sharia principles, there are variations in MMQ regulation and implementation. Practical challenges can be overcome by developing more detailed regulations, strengthening risk management systems, and increasing education and socialization to the public. Recommendations for improved regulation and MMQ practices include clearer regulation, increased training for bank staff, and product innovation. Further research is suggested to explore the social and economic impact of MMQ and the potential use of financial technology (fintech) in improving the efficiency and accessibility of MMQ. This research makes an important contribution to understanding and improving MMQ regulations and practices in Indonesia, Malaysia, and Brunei, as well as providing valuable recommendations for regulators and Islamic banking practitioners in the future